90. A COMSOL® multyphysics biomechanical model to simulate real parotid glands shrinkage during radiotherapy treatments. (December 2018) - Guidi, G.; Maffei, N.; Itta, F.; Ceroni, P.; D'Angelo, E.; Lohr, F.; Meduri, B.
Abstract : Purpose: To model and predict parotid gland (PG) deformation in H&N patients. A mesh-based approach was used to represent PG in 3Dstructure. The shape based estimation (SBE) model was employed to model and predict anatomical changes. The hypothesis was the knowledge of shape and deformation for training sample. The idea was to simulate shrinkage caused by radiation with mechanical force. Methods and materials: Raystation® hybrid deformation algorithms and 3DSlicer® tools were employed to obtain a mesh representation of PG anatomy and deformation from CTs of 8 H&N patients. Comparing planning kVCT and daily MVCTs the SBE model, implemented in Matlab®, utilizes the principal modes of co-variation between anatomy and deformation to forecast organ warping. Point-to-point correspondence between parotid meshes was obtained using the SPHARM-PDM approach. The biomechanical model has been mputationally implemented in COMSOL® multyphysics. Results: To test the predictivity of PG warping between the first and the last day, we used the leave-one-out cross validation method. The estimation error expressed in terms of DICE coefficient (DC) and RMSE between the true and predicted deformed mesh are 0.86 [0.84 ÷ 0.90] and 2.5 mm respectively. A mean volume decrease of 20.4% [10.1 ÷ 26.1%], principally localized on the external inferior region, was observed. The mean of the maximum vertex displacement along x, y, z is 6.5 ± 2.1 mm, 6.4 ± 1.5 mm, 6.1 ± 1.4 mm respectively. The best matching between real PG shrinkage due to radiation and the shrinkage due to the mechanical force, was obtained setting an intensity of 259 N and Young's modulus of 60, 00 Pa. Conclusion: The mesh surfaces study allows making analysis about parotid morphing dynamic and identify regions with greatest pattern of deformation. The choice of linear elastic model for soft tissue is reasonable because capsule and septa surrounding acinar cells are made of connective tissue rich in elastin. The predictive deformation model reached a prediction for 60% of the analysed cases. Weekly distance map of right parotid gland posteromedial region respect to start of treatment; red regions represent regions subjected to the highest displacement; distance value mm (right).